2020
DOI: 10.1038/s41598-020-63577-5
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol attenuates hypoxia-induced neuronal cell death, inflammation and mitochondrial oxidative stress by modulation of TRPM2 channel

Abstract: Hypoxia (HYpX) induced-overload ca 2+ entry results in increase of mitochondrial oxidative stress, inflammation and apoptosis in several neurons. Ca 2+ permeable TRPM2 channel was gated by ADPribose (ADPR) and reactive oxygen species (ROS), although its activity was modulated in HYPX-exposed neurons by resveratrol (RSV). The aim of this study was to evaluate if a therapy of RSV can modulate the effect of HYPX in the TRPM2 expressing SH-SY5Y neuronal and HEK293 (no expression of TRPM2) cell lines. The SH-SY5Y a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
68
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 55 publications
2
68
0
Order By: Relevance
“…Hypoxemia is a common cause of acute neuron injury. In the injured neuron area, massive inflammation and a large amount of proinflammatory cytokines are expressed, due to hypoxemia-induced oxidative stress and cell damage [ 10 , 11 ]. Treatment with anti-inflammatory reagents and neurotrophic factors becomes essential in the prevention and treatment of acute neuron injury in vivo [ 10 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypoxemia is a common cause of acute neuron injury. In the injured neuron area, massive inflammation and a large amount of proinflammatory cytokines are expressed, due to hypoxemia-induced oxidative stress and cell damage [ 10 , 11 ]. Treatment with anti-inflammatory reagents and neurotrophic factors becomes essential in the prevention and treatment of acute neuron injury in vivo [ 10 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the injured neuron area, massive inflammation and a large amount of proinflammatory cytokines are expressed, due to hypoxemia-induced oxidative stress and cell damage [ 10 , 11 ]. Treatment with anti-inflammatory reagents and neurotrophic factors becomes essential in the prevention and treatment of acute neuron injury in vivo [ 10 , 12 ]. Because it was previously reported that 3D in vitro culture promoted more efficient neuronal differentiation of stem cells, inducing more peripheral nerve regeneration than 2D in vitro culture [ 13 ], we in this study compared neuron cell growth in the 3D system and 2D system.…”
Section: Discussionmentioning
confidence: 99%
“…However, different RSV dosages preferentially activate SIRT1 or AMPK in vivo, further increasing the complexity of these pathways [ 113 ]. Besides the molecular mechanisms, studies based on preclinical neurodegenerative disease models reported positive effects of RSV in improving mitochondrial function and neurological symptoms [ 123 , 124 ]. More recently, the effects of RSV administration on mitochondrial respiration of skin fibroblasts from PMD-patients have been reviewed [ 125 ].…”
Section: “One-size-fits-all” Approachesmentioning
confidence: 99%
“…However, most of these members are non-selective cation channels which are responsible for the influx of monovalent and divalent ions, including Ca 2+ into the cell. Oxidative stress and reactive oxygen species (ROS) have also been postulated to play a role in mechanisms involving activation and inhibition of these TRP channels (Adhya and Sharma, 2019;Akyuva and Naziroglu, 2020). These properties make them an attractive target for the treatment of neurodegenerative conditions, including PD (Thapak et al, 2020c).…”
Section: Introductionmentioning
confidence: 99%